The prevalence and burden of bipolar disorder: findings from the Global Burden of Disease Study 2013 - Ferrari, Alize J; Stockings, Emily; Khoo, Jon-Paul; Erskine, Holly E; Degenhardt, Louisa; Vos, Theo; Whiteford, Harvey A (Bipolar disorders, 2016)
Objectives We present the global burden of bipolar disorder based on findings from the Global Burden of Disease Study 2013 (GBD 2013). Methods Data on the epidemiology of bipolar disorder were obtained from a systematic literature review and assembled using Bayesian meta‐regression modelling to produce prevalence by country, age, sex and year. Years lived with disability (YLDs) were estimated by multiplying prevalence by disability weights quantifying the severity of the health loss associated with bipolar disorder. As there were no years of life lost (YLLs) attributed to bipolar disorder, YLDs equated to disability‐adjusted life years (DALYs) as a measure of total burden. Results There were 32.7 million cases of bipolar disorder globally in 1990 and 48.8 million in 2013; equivalent to a 49.1% increase in prevalent cases, all accounted for by population increase and ageing. Bipolar disorder accounted for 9.9 million DALYs in 2013, explaining 0.4% of total DALYs and 1.3% of total YLDs. There were 5.5 million DALYs recorded for female individuals and 4.4 million for male individuals. DALYs were evident from age 10 years, peaked in the 20s, and decreased thereafter. DALYs were relatively constant geographically. Conclusions Despite being relatively rare, bipolar disorder is a disabling illness due to its early onset, severity and chronicity. Population growth and aging are leading to an increase in the burden of bipolar disorder over time. It is important that resources be directed towards improving the coverage of evidence‐based intervention strategies for bipolar disorder and establishing strategies to prevent new cases of the disorder.